109 Diet-induced Clinical Responsiveness of Translational Dog Model for Human Western Diet (WD)-related Disease Research. (8th October 2021) - Iennarella-Servantez, Chelsea A; Kathrani, Aarti; Sahoo, Dipak; Long, Elizabeth; Zdyrski, Christopher; Gabriel, Vojtech; Mao, Sichao; Bourgois-Mochel, Agnes; Resop, Mara; Rund, Lili; Rossoni-Serao, Mariana C; Jergens, Albert; et al.
Abstract: Human consumption of Western diets (WD) has been strongly associated with increased central obesity, adipocyte hypertrophy, intestinal epithelial stemness/proliferation, dyslipidemia, and blood pressure. These changes reflect metabolic dysfunction and contribute to increased risk of type 2 diabetes mellitus and colorectal cancer. As comprehensive molecular/clinical comparisons have not been performed, the objective of this study was to evaluate diet-induced changes in dogs as a clinically-responsive model for human WD-related disease research. Methods: In a crossover design, 10 dogs were fed either a 1.) control diet (CON) formulated based on the Acceptable Macronutrient Distribution Ranges and fiber recommendations for humans; or 2.) Western diet (WD) formulated based on National Health and Nutrition Examination Survey dataset parameters. Diets were prepared cooked with the same ingredients and formulated to meet/exceed nutrient/energy requirements for both humans/dogs and fed isocalorically based on calculated metabolizable energy (ME). Following each period ( 7–8 weeks), experimental parameters were measured. Results/Conclusions: Mean body weights were 8.83 and 9.28kg for CON and WD diets, respectively (P = 0.0018). Fasted (10-hour) blood samples differed significantly (P < 0.01) for mean fasting bile acids (CON=0.79, WD=8.94μmol/L), serum triglycerides (CON=45.70, WD=67.80mg/dL), and serum cholesterol (CON=140.10, WD=175.40mg/dL) demonstrating diet-dependent alterations in lipid profiles. Mean systolic blood pressures were 131.66 and 140.02mmHg for CON and WD, respectively (P < 0.0001). Histological analysis revealed diet-dependent changes in colonic epithelial villus height (CON=182, WD=207μm) and villus:crypt ratio (CON=2.61, WD=3.89). Preliminary RNA-ISH analysis (n = 3 dogs) showed increased LGR5+ expression (intestinal stem-cell marker) in WD compared to CON group (P = 0.0019) suggesting an increased "stemnness" of colonic epithelium. Further, mean adipocyte diameters were increased in omental fat biopsies (CON=58.6, WD=62.5μm; P < 0.0001) but not subcutaneous fat biopsies (P >0.05) following WD feeding, consistent with centralized obesity. Collectively, these results demonstrate effects of diet-induced changes in dogs as a clinically-responsive model for human WD-related disease research.